2015
DOI: 10.1016/j.anorl.2014.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Profile of parotid gland tumours: Experience of 93 cases over a period of 16 years

Abstract: Although there are features specific to the local context, the epidemiological profile of parotid tumours is well-known. Indications for complementary investigations are discussed, as availability in Senegal is restricted, highlighting the important role of clinical examination in the management of parotid tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 6 publications
1
7
0
3
Order By: Relevance
“…Salivary gland neoplasms constitute 5% of all head and neck neoplasms, and parotid gland neoplasms constitute 75% of the salivary gland neoplasms (Ho et al, 2011). In this 14 year period study, parotid gland neoplasms were found in patients with the age from 1st to 8th decade, and this in tandem with other similar studies worldwide (Diom et al, 2015;Altin et al, 2019;Stathopoulos et al, 2018;Tuckett et al, 2015). There was a slight overall female predominance with a male to female ratio of 1:1.2.…”
Section: Resultssupporting
confidence: 76%
“…Salivary gland neoplasms constitute 5% of all head and neck neoplasms, and parotid gland neoplasms constitute 75% of the salivary gland neoplasms (Ho et al, 2011). In this 14 year period study, parotid gland neoplasms were found in patients with the age from 1st to 8th decade, and this in tandem with other similar studies worldwide (Diom et al, 2015;Altin et al, 2019;Stathopoulos et al, 2018;Tuckett et al, 2015). There was a slight overall female predominance with a male to female ratio of 1:1.2.…”
Section: Resultssupporting
confidence: 76%
“…10 In this study males are predominantly affected as compared to females in both type of tumors i.e about 73%. But the results in other parts of world shows different results like the study carried out by ES Diom 11 shows females predominance where 61% cases occurred in females, another study of Maahs GS 10 also shows majority of patients as females.…”
Section: Discussionmentioning
confidence: 85%
“…Cliniquement une tumeur de la parotide peut se manifester par [ 5 ]: présence d'une masse ferme et décelable lors de la palpation généralement situé sous l'oreille et indolore; douleurs au niveau du visage, picotement, gênes; anomalies dans la motricité des muscles du visage; difficulté à avaler; paralysie faciale [ 6 ]. L a présence de métastase parotidienne rend la tumeur de mauvais pronostic selon les petites séries et les cas rapportés dans la littérature [ 7 , 8 ].…”
Section: Discussionunclassified